In vitro and in vivo evaluation of buccal bioadhesive films containing salbutamol sulphate - Singh S.; Soni R.; Rawat M.K.; Jain A.; Deshpande S.B.; Singh S.K.; Muthu M.S. (My University, 2025)
The aim of present study was to prepare and evaluate buccal bioadhesive films of salbutamol sulphate (SS) for the treatment of asthma. The films were designed to release the drug for a prolonged period of time so as to reduce the frequency of administration of the available conventional dosage forms of SS. The different proportions of sodium carboxymethylcellulose (SCMC) and Carbopol 940P (CP 940P) were used for the preparation of films. Carbopol was used to incorporate the desired bioadhesiveness in the films. The films were prepared by solvent casting method and evaluated for bioadhesion, in vitro drug release and anti asthmatic effect (bronchoprotection) in histamine induced bronchospasm of guinea pigs. In vitro drug release from the film was determined using a modified Franz diffusion cell while bioadhesiveness was evaluated with a modified two-arm balance using guinea pig buccal mucosa as a model tissue. Films containing SCMC : CP 940P ratio of 76 : 24 was found to be the best with moderate swelling along with favorable bioadhesion force and in vitro drug release. The drug release mechanism was found to follow non-Fickian diffusion as release mechanism. The prolonged in vivo effect (bronchoprotection) obtained from the buccal bioadhesive film of SS administered via buccal route may improve the treatment of asthmatic disorders by reducing the frequency of administration which is associated with the tolerance effect of SS. Additionally for the clinical benefit, it is also expected to reduce the major adverse effects of SS such as tachycardia and arrhythmias via buccal absorption. © 2010 Pharmaceutical Society of Japan.